THE IMPACT OF SMARTPHONE USE ON THE DEVELOPMENT OF ELEMENTARY SCHOOL STUDENTS' BEHAVIOR DURING THE COVID-19 PANDEMIC - Hendrowati, Tri Yuni; Huda, Miftachul (JLCEdu (Journal of Learning and Character Education), 2022)
This study aims to determine the impact of smartphone use on the development of elementary school students' behavior during the COVID-19 pandemic. The effect of using a smartphone is an impact or influence that can be beneficial or detrimental that arises as a result of a habit of using a smartphone. Meanwhile, the behavior of children who use smartphones is all actions or actions taken by children towards the use of smartphones. The impact of smartphone use on the current generation of the nation lies in the child who later grows up to be a leader. A leader who is able to lead himself is the most important factor. The thing that needs to be considered is character education that must be instilled early. This research uses qualitative descriptive methods as a stage in carrying out research. This research used data collection techniques including the observation, interview, documentation and recording stages. The data analysis used is a qualitative descriptive data analysis. The results showed that the use of smartphones by children is based on individual needs, especially during the Covid-19 pandemic, children's learning is all online.  Smartphones can be a means of learning and entertainment for children because they provide a lot of needed information. In addition to these beneficial things, the continued use of smartphones has a bad impact on children's behavior.